Prenatal exposure to organophosphorus pesticides and childhood neurodevelopmental phenotypes - Furlong, Melissa A. (Environ Res, 2017)
Prenatal exposure to organophosphorus pesticides (OPs) has been associated with different neurodevelopmental outcomes across different cohorts. A phenotypic approach may address some of these differences by incorporating information across scales and accounting for the complex correlational structure of neurodevelopmental outcomes. Additionally, Bayesian hierarchical modeling can account for confounding by collinear co-exposures. We use this framework to examine associations between prenatal exposure to OPs and behavior, executive functioning, and IQ assessed at age 6–9 years in a cohort of 404 mother/infant pairs recruited during pregnancy. We derived phenotypes of neurodevelopment with a factor analysis, and estimated associations between OP metabolites and these phenotypes in Bayesian hierarchical models for exposure mixtures. We report seven factors: 1) Impulsivity and Externalizing, 2) Executive Functioning, 3) Internalizing, 4) Perceptual Reasoning, 5) Adaptability, 6) Processing Speed, and 7) Verbal Intelligence. These, along with the Working Memory Index, were standardized and scaled so that positive values reflected positive attributes and negative values represented adverse outcomes. Standardized dimethylphosphate metabolites were negatively associated with Internalizing factor scores ( [Formula: see text] , 95% CI − 0.26, 0.00) but positively associated with Executive Functioning factor scores ( [Formula: see text] , 95% CI 0.04, 0.31). Standardized diethylphosphate metabolites were negatively associated with the Working Memory Index ( [Formula: see text] , 95% CI − 0.33, − 0.03). Associations with factor scores were generally stronger and more precise than associations with individual instrument-specific items. Factor analysis of outcomes may provide some advantages in etiological studies of childhood neurodevelopment by incorporating information across scales to reduce dimensionality and improve precision.